Strategi Filosofis Masyarakat Jepang Dalam Mengatasi Dilema Budaya Kerja Di Masa Pandemi Covid-19 - Iriyanto Widisuseno (KIRYOKU, 2021)
For the Japanese people, the remote work policy which aims to break the chain of the spread of the Corona-19 Virus is a cultural dilemma, because it clashes with the work culture of the people who have a strong work ethic. But in fact, Japan's economic recession rate is not as bad as other developed countries, such as America, China, and Korea. The death rate from Covid-19 is very low. Currently, Japan has started to return to the normal national economy. The mystery behind it all in Japan is the factor of superior immunity or cultural superiority. The assumption is, if because of the cultural superiority factor, what are the basic values that underlie the formation of behavior and culture of Japanese society. This philosophical qualitative study aims to examine philosophical strategies: what are the basic values that underlie the way Japanese people think and behave in the face of the Covid-19 pandemic, how to properly solve problems (epistemology), and what normative rules are used to give direction to achieve goals (axiology). Through philosophical descriptive methods, this research can reveal the philosophical values (ontological, epistemological, axiological) behind social phenomena in Japanese society. The results of the study show that Japanese people hold firmly to the value of discipline as an ontological footing, the samurai is used as a way to solve problems, the value of harmony as a normative rule that gives direction to the achievement of goals. The benefits of this research provide enlightenment for the community about understanding the basic problems in society that are often neglected, while many people only focus on the surface of the problem that causes failure to understand.